Determination of cores electrification during the flow in the modified Wurster apparatus - Ludwig, Wojciech; Mączka, Tadeusz (Technical Sciences, 2016)
The purpose of this paper was presentation of the value of cores electrification during their flow in the modified Wurster apparatus, applied for dry encapsulation of pharmaceutical materials. Previous works of the authors dealt with vulnerability of the particles of different diameter, produced by SYNTAPHARM (Cellets 1000, 700 and 100) on electrification in laboratory conditions. The presented work gives the results of examination on particles electrification in real conditions of their stable circulation in a column. The measurement system, that was applied, allowed determination of electrification potential and electrification current. Those quantities, which are the measures of charge accumulation on cores were determined for several particles (Cellets 1000, 700 and 500) with the different humidity, for different mass of the bed and spouting gas velocities.